Model checking-based safety verification for railway signal safety protocol-I. (1st January 2013) - Meng, Mei; Zhongwei, Xu; Xi, Wang; Yongbing, Wan
RSSP-I is one kind of safety communication protocol in signal system of China high-speed railways, which is needed to be verified in safety properties while assessing the whole system. Model checking is an effective way for verifying the safety properties of communication protocols. This paper proposes a new method based on labelled transition system (LTS) model checking for verifying the safety communication protocol's safety properties. First, it retrieves the safety requirement of RSSP-I, then adopts LTS to model the interaction behaviours in the system, after that, it analyses and verifies the safety properties of the model by means of LTSA (LTS analyser). The result of verification illustrates that the method can be efficiently applied to safety properties verification of protocol. Moreover, the method can be used to improve the designing and developing the safety protocols as well.